Mitochondrial DNA analyses of narrow-barred Spanish mackerel (Scomberomorus commerson) sampled from the Arabian Sea, the Bay of Bengal, and the Indo-Malay archipelago. Issue 3 (2nd October 2017) - Habib, Ahasan; Sulaiman, Zohrah
Abstract: The phylogeography of the narrow-barred Spanish mackerel ( Scomberomorus commerson ) in the Arabian Sea, Bay of Bengal, Indian Ocean, Java Sea, and South China Sea was investigated using sequence data from the mitochondrial DNA D-loop (control) region. Nucleotide diversities ranged from 0.04 to 0.095 in the study regions. Maximum-likelihood tree analyses supported three clades. Clade I was the major clade consisting of 100% of S. commerson individuals from the South China Sea, Indian Ocean, and Java Sea. Clade II consisted of 100% of individuals from the Arabian Sea and 20% from the Bay of Bengal. Lastly, Clade III was restricted to the Bay of Bengal populations. A significant pairwise F ST value (0.424) between the Bay of Bengal and South China Sea inferred a geographical isolation. This result can be used to understand the population structure of S. commerson populations using mitochondrial DNA in the Arabian Sea, Bay of Bengal and adjacent waters.